Obyek Kesukaan untuk Penempelan Telur (Oviposisi) Ektoparasit Argulus japonicus [ Preference Of Oviposition Object Of Ectoparasite Argulus japonicus] - Kismiyati Kismiyati; Nur Maulana Iskhaq; Juni Triastuti (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
Abstract A. japonicus is ectoparasite that attack only freshwater fish. The fish that was attacked by A. japonicus look skinny, always rub their body and appear some red spot that will manifest for second infection. Prevent and controll of A. japonicus, were used drug or chemical materials like insecticide. This compound can damage the environment and destroy surround ecosystem. Precisely metode to controll A. japonicus was focused for egg stage. The female habits of A. japonicus always lay her eggs (oviposition) on the surface object that surround on they habitat. The research using completely randomized design (CRD). The treatment on this research use 4 oviposition object like rock, wood, plants and PVC pipe. A rock that representative a hard and rough surface. Wood that representative rather solid state and irregular surface, plants with hard surface and representative a life organism (using Echinodorus palaefolius with wide and hard surface leaf), also PVC object that representative a hard and smooth surface. For comparator treatment, all oviposition object was collected in one treatment. All treatment were replicated at four times. Object was placed on bottom aquarium for use as oviposition object, to know preference of oviposition object by oviposition periode and totally eggs produced. ANOVA (analysis of variance) and Tukey-HSD range test were used to analyze data. Results showed that significant effect (p <0,05) on oviposition time and total eggs. The longest oviposition time and the higest eggs total was made by rock and pipe. The fastest oviposition time and the lowest eggs total was made by plants. Water quality during the study in optimum condition for A. japonicus and goldfish , temperature ranges from 26-28 0C, pH 7 and dissolved oxygen (DO) ranged at 5 mg/L.